2015
DOI: 10.1371/journal.pone.0137268
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence versus Statistical Modeling and Optimization of Cholesterol Oxidase Production by using Streptomyces Sp.

Abstract: Cholesterol oxidase (COD) is a bi-functional FAD-containing oxidoreductase which catalyzes the oxidation of cholesterol into 4-cholesten-3-one. The wider biological functions and clinical applications of COD have urged the screening, isolation and characterization of newer microbes from diverse habitats as a source of COD and optimization and over-production of COD for various uses. The practicability of statistical/ artificial intelligence techniques, such as response surface methodology (RSM), artificial neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…JRG-04 isolate. Similar to this study, production media optimization was also reported for a newly isolated species of Streptomyces identified to the genus level [24,25].…”
Section: Discussionsupporting
confidence: 79%
“…JRG-04 isolate. Similar to this study, production media optimization was also reported for a newly isolated species of Streptomyces identified to the genus level [24,25].…”
Section: Discussionsupporting
confidence: 79%
“…There are several studies that have compared RSM and ANN for modeling of different processes (Desai et al, ; Gomes & Awruch, ; Pathak et al, ; Youssefi, Emam‐Djomeh, & Mousavi, ). Both models were compared based on their capability of predicting both seen and unseen data.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical/AI approaches like RSM, ANN and GA are some popular techniques used in the optimization of various parameters like metabolite production, extraction condition etc. [16,17,37]. Response surface methodology is the most commonly used statistical technique used for depicting the nature of the response within the framed design space [17], whereas the genetic algorithm mimics the biological mutation process; hence it is based upon the biological principle of "survival of the fittest".…”
Section: Discussionmentioning
confidence: 99%